(untitled) (World Economics and Finance Bulletin, 2024)
The financial statements represent the primary and effective source for studying and determining the results of activity and the financial position of companies during the financial period. As a result of the further exacerbation of the problem of accounting manipulation and the display of financial statements in an unrealistic manner, and the increase in investors’ concerns about the lack of reliability and accuracy of the financial statements, the need for external auditing has arisen to strengthen Trust in the financial statements and reliance on them in making various decisions. Therefore, the research aims to shed light on identifying the impact of relying on the external auditing profession in limiting creative accounting practices. The study concluded that the auditing profession plays an effective role in verifying the fairness of financial statements, and thus limiting creative accounting practices. The auditor performs many procedures that lead to the auditor verifying the fairness and honesty of the financial statements and their expression of the financial position of the facility, thus limiting creative accounting practices. Therefore, the study recommends the necessity of educating and familiarizing practitioners of the auditing profession with modern methods that help in revealing creative accounting practices